2013
DOI: 10.21608/jpp.2013.73726
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SOME ORGANIC AND BIO-FERTILIZERS ON QUALITY AND QUANTILY OF Rosmarinus officinalis L. PLANTS

Abstract: Two field experiments were carried out on rosemary plants (Rosmarinus officinalis L.) at the experimental Baramoon Research Farm, Dakahlya Governorate, Egypt, during two successive seasons, 2010-2011 and 2011-2012, , to study the effect of different sources of organic manure (FYM) mixed of poultry and cattle manures, humic acid, biofertilization nitrogen fixing bacteria (microbein) and phosphate dissolving bacteria (phosphorein), as well as active dry yeast on vegetative growth, herb yield, essential oil prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Kassem (2013) reported that active dry yeast significantly boosted plant growth as measured by plant height, branch number per plant, and fresh and dry weights per plant. According to Sharaf et al (2013), treating plants with active dry yeast resulted in much higher growth and yield than untreated plants. Khalil & Khalil (2015) studied the role of active dry yeast in water stress mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Kassem (2013) reported that active dry yeast significantly boosted plant growth as measured by plant height, branch number per plant, and fresh and dry weights per plant. According to Sharaf et al (2013), treating plants with active dry yeast resulted in much higher growth and yield than untreated plants. Khalil & Khalil (2015) studied the role of active dry yeast in water stress mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of humic acid improved the output of essential oils as proved by Sharaf ElDin et al (2013), Jalayerinia et al (2017), and Zghair et al (2022 on rosemary plants.…”
mentioning
confidence: 87%
“…The significant effects of biofertilizers are due to the different groups of strains, which help in the availability of nutrients in the available forms and increase the minerals levels in the soil. (Sharaf EL- Din et al, 2013).…”
Section: Introductionmentioning
confidence: 99%